Plan de exportación de mango a Canadá (2020)
The purpose of this research work is to identify the viability for mango exports to Canada, based on a competitive business model and a market analysis. In this sense, the work seeks to serve as an application model and / or initial consultation to mango cultivation projects that seek to export to Canada and be internationally competitive. In this way, the established methodology is constituted from a theoretical or fundamental investigation, which consists on the analysis of knowledge of a phenomenon, through an explanatory principle of observable reality. Following this logic, the conclusions reached indicate that Colombia is a country that due to its geographical location and climatic nature has a high productivity in the agricultural sector. However, and although it has great advantages for agricultural production, its efforts in rural progress have been insufficient and mostly ineffective in positioning itself as a competitive economy in the agricultural sector at the international level. For this reason, the research and technological models can mean for the country an advance in mango exports.